Natural fibre in improving rheology of drilling fluid: a review / Nik Khairul Irfan Nik Ab Lah, Mohammad Fikri Husaili and Effah Yahya - Nik Ab Lah, Nik Khairul Irfan; Husaili, Mohammad Fikri; Yahya, Effah (Universiti Teknologi MARA Shah Alam, 2022)
Drilling phase is one of important phase in development plan to avoid unintended loss such as loss circulation. Loss circulation can cause drilling downtime, affected the formation condition and most probably the cost of drilling program. To overcome these problems, one of the alternatives is by adding fluid loss additive (LCM). Somehow, the conventional additive such Polyanionic-Cellulose (PAC) are mostly the first choice as LCM to curb the loss circulation problem, but other problem arises such as environmental pollution due to unfriendly additive. Hence, many research has study the alternative way to replace conventional additive. Hence this paper objective is to analyse on the natural fibre as the potential additive to reduce the loss circulation problem and suggest any improvement that can be done to the studies. From the analysis, the natural fibre has huge impact on the drilling fluid rheology and other properties. Most of the natural fibre can surpass the value of rheology properties in plastic viscosity, yield point and gel strength with certain value or size of material that indicate as concentration. Also, natural fibre modification on drilling fluid gives a big impact in fluid loss control.